Indian economic thought and development. - "Bhuleshkar, Ashok V(ed)" (Bombay, 1969)
I say with passion because I believe in the progress of India. I want to do something in India to change India within the few years left to me, to change the peasant in India, to change agriculture, economy and the rest.
Keywords: Economic development .